A Contrastive Analysis Of Adjective Clause In English And Indonesia On Explanation Text - Citra Julivera Nainggolan; Kesia Rahelin Simanjuntak; Grace Siadari; Okta Jagardo Sitompul (Jurnal Ilmu Pendidikan dan Sosial, 2023)
This research aims to determine the ability of students of the 6th semester English study program at HKBP Nommensen Pematangsiantar University in using adjective clauses in Indonesian and English. This research aims to show the dominant function and types of adjective clauses in explanatory text. Apart from that, this journal also shows differences in the use of adjective clauses between English and Indonesian. Researchers looked at adjective-clause material based on English and Indonesian. The method used in this research is called library research, or in other words library research. From this research it can be concluded that the number of words most often found in the use of adjective clauses for explanatory text is 7, with a total of 7 words from 10 sentences. In Indonesia, 7 words out of 10 sentences. This means that, in both English and Indonesian, adjective clauses in explanatory texts have differences and similarities between English and Indonesian.